Homing endonucleases: structure, function and evolution - Jurica, M. S.; Stoddard, B. L. (Cellular and molecular life sciences : CMLS, 1999)
'Homing' is the lateral transfer of an intervening genetic sequence, either an intron or an intein, to a cognate allele that lacks that element. The end result of homing is the duplication of the intervening sequence. The process is initiated by site-specific endonucleases that are encoded by open reading frames within the mobile elements. Several features of these proteins make them attractive subjects for structural and functional studies. First, these endonucleases, while unique, may be contrasted with a variety of enzymes involved in nucleic acid strand breakage and rearrangement, particularly restriction endonucleases. Second, because they are encoded within the intervening sequence, there are interesting limitations on the position and length of their open reading frames, and therefore on their structures. Third, these enzymes display a unique strategy of flexible recognition of very long DNA target sites. This strategy allows these sequences to minimize nonspecific cleavage within the host genome, while maximizing the ability of the endonuclease to cleave closely related variants of the homing site. Recent studies explain a great deal about the biochemical and genetic mechanisms of homing, and also about the structure and function of several representative members of the homing endonuclease families.